Targeted Radiotherapy of the Tumor Cavity after Surgical Resection of Aggressive Recurrent Brain Metastasis: A Case Report - Fadrus, Pavel; Kazda, Tomas; Dvoracek, Petr; Pospisil, Petr; Hynkova, Ludmila; Zitterbartova, Jana; Dymackova, Radana; Kolouskova, Ivana; Belanova, Renata; Prochazka, Tomas; Slampa, Pavel (Case reports in oncology, 2020)
Postoperative management of patients with brain metastases is controversial. Besides local control, cognitive function and quality of life are the most important outcomes of postoperative radiotherapy. In this case report, we introduce a patient with aggressive recurred solid metastasis treated with repeated surgery and an individual radiotherapy approach in order to highlight that close mutual collaboration leads to a clear benefit for our patients. The local targeted radiotherapy with 35 Gy in 10 fractions was performed with the volumetric modulated arc technique, leading to more than 2.5 years of local control and survival without any of the side effects usually attributed to whole brain radiotherapy.
Keywords: Radiotherapy; Brain metastases; Local control